2019
DOI: 10.3390/biomedicines7030058
|View full text |Cite
|
Sign up to set email alerts
|

Role of Muscarinic Acetylcholine Signaling in Gastrointestinal Cancers

Abstract: In the tumor microenvironment, various stromal and immune cells accumulate and interact with cancer cells to contribute to tumor progression. Among stromal players, nerves have recently been recognized as key regulators of tumor growth. More neurotransmitters, such as catecholamines and acetylcholine (ACh), are present in tumors, as the cells that secrete neurotransmitters accumulate by the release of neurotrophic factors from cancer cells. In this short review, we focus on the role of nerve signaling in gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Recruitment, growth, or differentiation of CAFs and blood vessels is caused by numerous interactions between tumor cells and other stromal components. Recent studies have suggested that nerves and neurotransmitters also play a critical role within the tumor microenvironment for many cancers, including gastric cancers 109‐115 . Some tumor stromal components may be anti‐tumorigenic, 7,58,116 but tumor cells and other stromal cells appear to acquire the ability to escape this anti‐tumorigenic host defense.…”
Section: Resultsmentioning
confidence: 99%
“…Recruitment, growth, or differentiation of CAFs and blood vessels is caused by numerous interactions between tumor cells and other stromal components. Recent studies have suggested that nerves and neurotransmitters also play a critical role within the tumor microenvironment for many cancers, including gastric cancers 109‐115 . Some tumor stromal components may be anti‐tumorigenic, 7,58,116 but tumor cells and other stromal cells appear to acquire the ability to escape this anti‐tumorigenic host defense.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylcholine is the most important excitatory neurotransmitter in the gastrointestinal nervous system. It can excite the smooth muscle of the gastrointestinal tract and thus depolarize the cell membrane of the smooth muscle [15,16]. Atropine sulfate can block the excitatory action of muscarinic receptors to inhibit acetylcholine, thereby reducing the excitability of the gastrointestinal smooth muscle, and reducing the amplitude and frequency of gastrointestinal peristalsis [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Although tuft cells were firstly discovered in rat trachea, they have been well described in most mucosal epithelia. In rodents, they have been found through respiratory system (nasal cavity Finger et al, 2003 ; Ogura et al, 2010 , and trachea Krasteva et al, 2011 ; Saunders et al, 2013 ) to the digestive system (salivary glands ( Sato and Miyoshi, 1988 ), gastrointestinal tract ( Bezencon et al, 2008 ; Schütz et al, 2015 ; Hayakawa et al, 2017 ; Konishi et al, 2019 ), biliary tract ( Schütz et al, 2015 ) and colon ( Silva, 1966 ; Howitt et al, 2016 ) and the urogenital tract ( Deckmann et al, 2015 ), as well as the thymus ( Panneck et al, 2014 ), auditory tube ( Krasteva et al, 2012b ), and taste buds ( Sukumaran et al, 2017 ).…”
Section: Characteristics Of Tuft Cellsmentioning
confidence: 99%
“…This abnormal cholinergic signaling regulates Wnt and YAP pathways to promote the initiation of tumors. The shift in tuft cells and cholinergic innervation suggests that tuft cells, in part, interfere tumor initiation in the early stage ( Hayakawa et al, 2017 ; Konishi et al, 2019 ).…”
Section: Pathophysiological Roles Of Ach Produced By Tuft Cellsmentioning
confidence: 99%
See 1 more Smart Citation